Improving health-related quality of life among people living with HIV: Results from an impact evaluation of a food assistance program in Uganda - Maluccio, John A.; Palermo, Tia; Kadiyala, Suneetha; Rawat, Rahul (Public Library of Science, 2015)
Introduction Widespread food insecurity in Africa continues to compromise an effective response to the AIDS epidemic. Health-related quality of life (HRQoL) is a comprehensive indicator of physical, mental, and social well-being that is associated with food insecurity and increasingly used to assess the well-being of people living with HIV/AIDS (PLHIV). We examined the impact of a food assistance intervention, previously shown to have reduced household food insecurity and improved nutritional status, on HRQoL of PLHIV. Methods We capitalized on an existing intervention targeting antiretroviral therapy (ART)- naïve PLHIV in Uganda, and conducted a prospective impact evaluation including a treatment and a comparison group. Data analyzed included 640 participants from two districts (318 in the intervention district) interviewed in both clinic and household settings at baseline and again approximately one year later. The main outcomes considered were physical and mental health dimensions of HRQoL, and other outcomes included self- and healthcare provider-reported symptoms. We utilized difference-in-difference propensity score matching methodologies to infer causality and examine program impacts. Results Over 12 months, food assistance significantly increased physical health scores (PHS) by 2.85 (P < .01) or approximately 0.35 SD, and reduced substantially the number of self- and healthcare provider-reported HIV-related symptoms by 3.83 and 2.68, respectively (P < .01). There was no significant impact, however, on mental health scores (MHS). Conclusions This study demonstrates the potential importance for HRQoL of including food assistance programming as part of the standard of care for PLHIV in areas of widespread food insecurity.